Evaluation of incidence bone fracture with Purabone as an osteoinductive material in comparison with Tricalcium Phosphate in obliteration of endophytic mandibular cysts : Randomized controlled clinical study - Mohamed Mohsen Hussein Elbanna; Samar Sewilam; Sherif Ali (Cairo : Mohamed Mohsen Hussein Elbanna, 2019)
Purpose: The aim of this study is to evaluation of Purabone as an osteoinductive material in comparison with Tricalcium phosphate in obliteration of endophytic mandibular cysts Materials and method: Twelve patients were selected from the outpatient clinic of Oral and Maxillofacial surgery at Faculty of Dentistry, Cairo University during the period from 2015 through 2017. Result: Estimation of 6 months postoperative conventional CT scans for all patients we found that 100% of patients in control group (Group B) had increase in radiodensity while 66.7% of patients in intervention group (Group A) had increase in radiodensity Conclusion: Increasing the feasibility of plant derived materials with osteoinductive properties that aids in bone regeneration. Purabone in collagen matrix has the effect of increasing new bone formation. Tricalcium phosphate had better results in bone formation in comparison with Purabone. Plant derived Purabone xenograft became realistic and this will change the view of surgeons towards xenografts
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral and Maxillofacial Surgery
Issued also as CD
Keywords: Incidence bone fracture; Purabone; Tricalcium Phosphate